Vitamin D deficiency linked to abnormal bone and lipid metabolism predicts high-risk multiple myeloma with poorer prognosis - Bao, Li; Wang, Yu-tong; Lu, Min-qiu; Chu, Bin; Shi, Lei; Gao, Shan; Fang, Li-juan; Xiang, Qiu-qing; Ding, Yue-hua; Liu, Xi; Zhao, Xin; Wang, Meng-zhen; et al. (Frontiers in Endocrinology, 2023)
Purpose: Vitamin D deficiency is frequent in patients with multiple myeloma (MM), however, its prognostic relevance in MM was rather inconclusive. We first investigated the association of vitamin D deficiency with abnormal bone and lipid metabolism in newly diagnosed multiple myeloma (NDMM), and next assessed the impact of serum ratio of vitamin D to carboxy-terminal telopeptide of type I collagen (β-CTX) on progression-free survival (PFS) and overall free survival (OS) in patients with NDMM. Methods: The data of 431 consecutive patients with NDMM at Beijing Jishuitan Hospital from September 2013 to December 2022 were collected and retrospectively reviewed through our electronic medical record system. The measurement of 25-hydroxyvitamin D in the blood is an indicator of an individual's overall vitamin D status. Results: The serum levels of vitamin D were negatively correlated with β-CTX in NDMM patients. Of note, positive correlation between vitamin D and cholesterol levels in the serum was found in this study. The cohort (n = 431) was divided into two groups based on the serum ratio of vitamin D to β-CTX. Compared to the group with a higher vitamin D to β-CTX ratio, the group with a lower vitamin D to β-CTX ratio (n = 257, 60%) exhibited hypocholesterolemia, inferior PFS and OS, along with increased cases of ISS stage-III and R-ISS stage-III, a higher number of plasma cells in the bone marrow, and elevated serum calcium levels. Consistent with this, multivariate analysis confirmed that the vitamin D to β-CTX ratio was an independent unfavorable indicator for survival in NDMM patients. Conclusion: Our data demonstrated the ratio of vitamin D to β-CTX in the serum is a unique biomarker for NDMM patients to identify the high-risk cases with poor prognosis, which is superior to vitamin D itself for predicting PFS and OS in NDMM. Also, it is worth mentioning that our data on the connection between vitamin D deficiency and hypocholesterolemia might help clarify novel mechanistic aspects of myeloma development.